The efficacy scheduling formats on achievement of high school students - Bowman, Jed R., author; Cobb, Brian, advisor; Ginsberg, Rick, committee member; Lewis, Chance W., committee member; Long, Kelly, committee member (Colorado State University. Libraries, 2005)
The purpose of this dissertation was to contribute an empirically sound longitudinal study on the effects of scheduling formats on high school student achievement as measured by performance on ACT mathematics and reading subtests. School of choice allowed a unique longitudinal design to explore achievement and schedule format combination. Secondary schools utilized traditional, AB block, and 4x4 block schedule formats resulting in nine junior/senior high school combinations. Two combinations were eliminated from the final sample due to small n's. An analysis of covariance (ANCOVA) was used, and achievement was controlled using 6th grade mathematic and reading Achievement Level Tests before students entered the schedule format combination intervention. Before using ANCOVA, assumptions were tested and when violated, a forward multiple regression analysis was conducted. In mathematics, a statistically significant post hoc result for one schedule format combination showed students with the traditional schedule format had higher mean scores than students with the 4x4 block schedule format. Effects were examined by gender and FRL status, and there were no interactions. In reading, two statistically significant post hoc results showed students in the traditional schedule format had higher mean scores than students with either block schedule format schools. These effects were examined by gender and FRL status, and no interactions were found. Supplemental analyses conducted to study the effect of schedule format stability used the same outcome measures. Results showed students who changed formats had higher mean scores in mathematics than students who remained in the same format. When these effects were examined by gender and FRL status, there were no interactions. In reading, there were no significant findings. Results suggest higher achievement in mathematics and reading in the traditional format school; however, caution should be exercised as no definitive trends or patterns were observed across samples and few pairwise contrasts contributed. Broad generalizations are difficult to make as this study utilized archived results from one school district. Statistically robust longitudinal studies are recommended. Additionally, replication studies are encouraged to observe patterns over time.
Keywords: secondary education; school administration; educational administration